Determination of Fractionation Scheme Based on Repair Effect Using Equivalent Uniform Dose (EUD) Model - Pratista, Tiara Andrina; Widita, Rena (Indonesian Journal of Physics, 2023)
Radiotherapy treatment planning is required to obtain an optimal balance between delivering a high dose to target volume and a low dose to organ at risks. In this planning, it is also necessary to determine the appropriate fractionation scheme for each patient. One of the commonly used methods to determine the fractionation scheme is calculating the Normal Tissue Complication Probability (NTCP) and Tumor Control Probability (TCP) parameters. In this study, the Equivalent Uniform Dose (EUD) model is used to calculate NTCP and TCP. This model is based on a non-uniform dose distribution that is sensitive to the biological factors of cells. The biological factor examined in this research is the repair effect, which is the ability of cells to repair themselves after being radiated. Thus, the objective of this research is to determine the fractionation scheme based on NTCP calculations using the EUD model while taking into account the repair effect. The data used in this study were obtained from 10 patients with glioblastoma brain cancer in the form of cumulative DVH (dose-volume histogram) and total time of radiation. Based on the NTCP calculations, the average risk of organ complication for each patient appears to be close to zero, with a range of values from 2 x 10-6% to 1 x 10-1%. These results indicate that the treatment planning conducted is proven to be safe and there are no complications for the patients. Furthermore, based on the NTCP and TCP calculations, the best fractionation scheme is hypofractionation, which remains safe while considering the dose limit for each normal organ surrounding the target.